2018
DOI: 10.3897/mycokeys.39.26914
|View full text |Cite
|
Sign up to set email alerts
|

High diversity of Diaporthe species associated with dieback diseases in China, with twelve new species described

Abstract: Diaporthe species have often been reported as important plant pathogens, saprobes and endophytes on a wide range of plant hosts. Although several Diaporthe species have been recorded in China, little is known about species able to infect forest trees. Therefore, extensive surveys were recently conducted in Beijing, Heilongjiang, Jiangsu, Jiangxi, Shaanxi and Zhejiang Provinces. The current results emphasised on 15 species from 42 representative isolates involving 16 host genera using comparisons of DNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 66 publications
(156 reference statements)
4
112
0
Order By: Relevance
“…Diaporthe includes several endophytic, saprotrophic and phytopathogenic species on a wide range of hosts [5][6][7]. Pathogenic species on forest and ornamental trees usually have been reported causing canker and dieback diseases [15,50]. Although the novel species described here were isolated from necrotic leaf spots and branch showing dieback, their pathogenicity should be evaluated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Diaporthe includes several endophytic, saprotrophic and phytopathogenic species on a wide range of hosts [5][6][7]. Pathogenic species on forest and ornamental trees usually have been reported causing canker and dieback diseases [15,50]. Although the novel species described here were isolated from necrotic leaf spots and branch showing dieback, their pathogenicity should be evaluated.…”
Section: Discussionmentioning
confidence: 95%
“…Some species are responsible for severe diebacks, cankers, leaf-spots, blights, melanoses, stem-end rot and gummosis on different woody and herbaceous hosts [6,[8][9][10]. With the extensive use of DNA sequence-based methods for studying the genus in the last decade [11], the occurrence of Diaporthe species in natural forest ecosystems has increased noticeably, with new descriptions in Australia, Brazil, Canada, China, Japan, Portugal, La Rèunion, South Africa, Thailand, Tanzania and Zambia [12][13][14][15][16][17][18]. Among these, Diaporthe virgiliae is an emerging disease causing the death of endemic Virgilia oroboides trees in South Africa [19].…”
Section: Introductionmentioning
confidence: 99%
“…The current study focuses on Diatrypaceae species in China, which is considered as a biodiversity hotspot with a high diversity for fungal species (Yang et al 2018;Fan et al 2020;Pan et al 2020). We hope that the descriptions and molecular data of Diatrypaceae in this study could provide a resource for future studies in this family.…”
Section: Discussionmentioning
confidence: 99%
“…Notes -The genus Diaporthe has been widely revised, with new species frequently being described (Gomes et al 2013;Gao et al 2015;Yang et al 2018). The strain URM 7972 was isolated from leaves of Myracrodruon urundeuva in Brazil (Pádua et al 2018) and identified as Diaporthe myracrodruonis sp.…”
Section: Diaporthe Myracrodruonismentioning
confidence: 99%